Perceived trustworthiness of faces drives trust behaviour in children. Issue 2 (22nd July 2014) - Ewing, Louise; Caulfield, Frances; Read, Ainsley; Rhodes, Gillian
Abstract Facial appearances can powerfully influence adults' trust behaviour, despite limited evidence that these cues constitute honest signals of trustworthiness. It is not clear, however, whether the same is also true for children. The current study investigated whether, like adults, 5‐year‐olds and 10‐year‐olds are more likely to place their trust in partners that look trustworthy than those that look untrustworthy. A second, closely related question was whether children also explicitly value the information from face cues when making trust decisions. We investigated these questions using Token Quest: an economic trust game that gave participants the opportunity to make investments with a series of partners who might (or might not) repay their trust with large returns. These interactions occurred under different conditions, including one in which participants were shown the face of each partner and another in which they could 'purchase' access to faces with a portion of their investment capital. Results indicated that, like adults, 10‐year‐old children selectively placed their trust in those partners they perceived as looking trustworthy and many were willing to 'pay' to purchase access to these face cues during the trust game. We observed a similar profile of trust behaviour in 5‐year‐olds, with no significant group difference in the impact of face cues on behaviour across the three age groups. Together, these findings indicate that the influence of face cues on trust behaviour emerges early, and highlight a capacity for sophisticated social cognition in young children.